2013
DOI: 10.1186/gb-2013-14-7-r75
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes with age in skin, adipose tissue, blood and brain

Abstract: BackgroundPrevious studies have demonstrated that gene expression levels change with age. These changes are hypothesized to influence the aging rate of an individual. We analyzed gene expression changes with age in abdominal skin, subcutaneous adipose tissue and lymphoblastoid cell lines in 856 female twins in the age range of 39-85 years. Additionally, we investigated genotypic variants involved in genotype-by-age interactions to understand how the genomic regulation of gene expression alters with age.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
235
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(260 citation statements)
references
References 56 publications
22
235
3
Order By: Relevance
“…New world monkeys (Parvorder Platyrrhini). Agedependent Ab deposition has been reported in new world monkeys, such as common squirrel monkeys (Saimiri sciureus), 27 common marmosets (Callithrix jacchus), 55 and tamarins (Saguinus spp.). 48 New world monkeys are smaller than old world monkeys, have shorter life spans, and develop Ab deposits earlier.…”
Section: Old World Monkeys (Superfamily Cercopithecoidea)mentioning
confidence: 99%
See 1 more Smart Citation
“…New world monkeys (Parvorder Platyrrhini). Agedependent Ab deposition has been reported in new world monkeys, such as common squirrel monkeys (Saimiri sciureus), 27 common marmosets (Callithrix jacchus), 55 and tamarins (Saguinus spp.). 48 New world monkeys are smaller than old world monkeys, have shorter life spans, and develop Ab deposits earlier.…”
Section: Old World Monkeys (Superfamily Cercopithecoidea)mentioning
confidence: 99%
“…55,110 While many biological changes may contribute to this degree of variability, antioxidant status and regenerative capability are probably the most important biological factors that determine the response of a certain tissue or organ to the aging process. 37,172,184 Brain is probably the most vulnerable tissue affected by aging because of its high oxygen requirement, low synthetic capacity of endogenous antioxidants, and limited regeneration capability.…”
mentioning
confidence: 99%
“…Extensive studies in model organisms and human tissues have identified many genes that show age-dependent expression changes (Lee et al 1999;Zou et al 2000;Kayo et al 2001;Pletcher et al 2002;McCarroll et al 2004;Zahn et al 2006;Golden and Melov 2007;Budovskaya et al 2008;Hong et al 2008;de Magalhaes et al 2009;Glass et al 2013). These age-regulated genes generally participate in a wide variety of biological processes that are associated with age-dependent physiological changes.…”
mentioning
confidence: 99%
“…(2008) identified several thousand age‐related changes in gene expression in four different brain tissues. Later studies by different groups identified profound changes in the transcriptome with age in further tissues, such as skin, adipose tissue ( N  = 865) (Glass et al ., 2013) and kidney ( N  = 134) (Rodwell et al ., 2004). Most of these changes did not overlap in different tissues.…”
Section: Omics and Agingmentioning
confidence: 99%